Differential Expression of IGF Family Members in Heat‐Stressed Embryos Produced In Vitro from OPU‐Derived Oocytes of Nelore (Bos indicus) and Holstein (Bos taurus) Cows. Issue 6 (24th July 2013) - Satrapa, RA; Razza, EM; Castilho, ACS; Simões, RAL; Silva, CF; Nabhan, T; Pegorer, MF; Barros, CM
Contents: The IGF system is related to embryo quality. We aim to determine the effect of the heat stress on the mRNA expression of IGF1 and IGF2, IGFR1 and IGFR2, IGFBP2 and IGFBP4, and PAPPA in in vitro production (IVP) blastocysts from Nelore and Holstein after ovum pick up (OPU) to better understand the differences between these breeds. Oocytes from four Nelore and seven Holstein were collected in six OPU sessions. Following in vitro maturation and fertilization using six Nelore or Holstein sires, embryos were divided into control (cultured at 39°C) and heat stress (HS; exposed to 41°C for 9 h). Blastocysts were submitted to RNA extraction. The IGF1 expression was higher in blastocysts under HS in both breeds, and the expression of IGFBP2 and IGFBP4 was higher in Holstein blastocysts under HS. The high PAPPA expression and the low expression of IGFBP2 and IGFBP4 are associated with a more efficient degradation of IGFBP s, which results in greater IGF bioavailability in Nelore blastocysts and may contribute to the superior HS tolerance in Nelore, when compared to Holstein.